Neue Aspekte bei der Einlagerung von Beute durch die solitäre Wespe Symmorphus crassicornis (Panzer) in ihre Brutzellen (Hymenoptera, Vespidae, Eumenidae). - Tölke, Arnim (Contributions to Entomology = Beiträge zur Entomologie, 2007)
The author managed to lure Symmorphus crassicornis (Panzer) into a bamboo nest tube, the central part of which had been replaced by a 5 cm long acrylic tube. Visual observation made possible in this way enabled the author to find out that the solitary wasp does not usually sort its prey immediately into the brood cell. Rather, it catches a certain quantity of sawfly larvae and deposits them first in front of the brood cell inside the breeding tube. The egg, suspended on a filament hanging down from the ceiling of the brood cell, is not being contacted in any case. In this phase the wasp deposits the caught larves either individually one behind the other or even occasionally – when these are of a certain size – one alongside the other, but never one upon the other. The wasp does not start sorting the prey into the brood cell until it has carried a certain quantity of prey to the space in front of it. In doing so, it takes the prey with its mandibles and pulls it, walking backward, into the brood cell. It always chooses the largest caterpillar first, then the second largest, etc. It is also worth mentioning that the wasp always removes all caterpillars lying in front of the brood cell irrespectively of how full the brood cell actually is. That means that not a single item of prey remains outside the brood cell. If the wasp has difficulty pulling the prey, it switches from pulling to pushing. If the brood cell is very full, it occasionally happens that the wasp removes a caterpillar from it and tries a different kind of sorting. The egg contact proved before (Tölke, A. 1996) in respect of Symmorphus crassicornis (Panzer), which happens so that the wasp uses one of its antennae to strike against the freely suspended egg, making it oscillate so that it effects a pendulum-type rebound, which the wasp intercepts using the same antenna, plays a completely different role than has been assumed so far in controlling the prey to be sorted into the nest. For if, due to a high filling level reached after the last deposited caterpillar was sorted into the nest, the wasp does not feel the egg rebound, it closes the brood cell with loam. But even if the wasp cannot strike against the egg because of particular circumstances, notwithstanding it closes this brood cell, when all caterpillars in front of it have been sorted into the nest. The author managed to prove this behaviour also indirectly by way of an experiment, rotating a bamboo tube, occupied by a wasp, 180 degrees each time a new brood cell had been built and the egg had been laid. As a consequence, the egg lay on the floor of the brood cell and a strike causing the pendulum-type rebound was not possible. But even under such circumstances the cell was not closed immediately, but, as usually, only after all sawfly larvae deposited in the front area of the nest had been sorted into the brood cell. However, if a prey-sorting wasp under normal nesting conditions effects the pendulum-type strike described above and also feels the rebound, it once again proceeds to the hunting phase and, as a first step, deposits the prey it has caught in the breeding tube in front of the brood cell, as described, and finally sorts these larves into the brood cell as well, as described above.